2009
DOI: 10.1111/j.1365-2672.2009.04205.x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of the antibacterial and antifungal activities of aspirin, EDTA and aspirin-EDTA combination and their effectiveness as antibiofilm agents

Abstract: Aims:  To evaluate the antimicrobial activities of aspirin, EDTA and an aspirin‐EDTA (A‐EDTA) combination against Pseudomonas aeruginosa, Escherichia coli and Candida albicans in planktonic and biofilm cultures. Methods and Results:  Minimal inhibitory concentrations (MIC) and minimal biocidal concentrations (MBC) were determined using twofold broth microdilution and viable counting methods, respectively. Aspirin’s recorded MIC values ranged from 1·2 to 2·7 mg ml−1. Checkerboard assay demonstrated a synergism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 29 publications
2
50
1
4
Order By: Relevance
“…Earlier studies have shown that 50 mM EDTA disrupts the biofilm [21][22][23]. Contrary to these, we found that 10 mM EDTA disrupts the bacterial biofilm when tested alone; the concentration of EDTA used in our study was five times lower than previous study.…”
Section: Antimicrobial Agent Percentage (%) Of Isolatescontrasting
confidence: 56%
“…Earlier studies have shown that 50 mM EDTA disrupts the biofilm [21][22][23]. Contrary to these, we found that 10 mM EDTA disrupts the bacterial biofilm when tested alone; the concentration of EDTA used in our study was five times lower than previous study.…”
Section: Antimicrobial Agent Percentage (%) Of Isolatescontrasting
confidence: 56%
“…Although EDTA is typically considered as a ''nonantibiotic'' agent and used in endodontics to remove the smear layer for improved sealing during root filling (21), recent studies have shown antimicrobial effects of EDTA against microorganisms in biofilms (22,23). Although the mode of action of EDTA in this respect is still not clarified, the chelating effect to calcium and iron may affect important metabolic pathways in the bacterial cell (24).…”
Section: Discussionmentioning
confidence: 99%
“…Although EDTA is one of the most commonly used, its antimicrobial activity against biofilms is a matter of some controversy (9,11,15). Maleic acid (MA), a mild organic acid, has been more recently proposed for use as a final irrigating solution, as an alternative to EDTA (16), because of its better smear layer removal from the apical third of the root canal system (17) and its lower toxicity (16).…”
mentioning
confidence: 99%